Analisis Bibliometrik ANALISIS BIBLIOMETRIK: TREN DAN PERSPEKTIF PENELITIAN PENDIDIKAN PEDAGOGI DI ERA DIGITAL (2014-2024) - Sumara, Andry Rivan; Yusrizal; Arsyad; Budiwati, Neti (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
The examination of pedagogy is crucial due to its substantial influence on educational learning frameworks. Digital advancements profoundly affect pedagogical methodologies. Consequently, comprehensive investigations regarding pedagogical research trends in the digital era over the past ten years are essential. A bibliometric analysis seeks to delineate research pertaining to pedagogy within the digital context. Data is sourced from the Scopus database, focusing on educational and digital subjects, specifically through queries of "Pedagogical," "E-learning," and "Education" in English, encompassing published articles. The data extraction yielded 1,996 articles for subsequent analysis. Findings indicate a notable surge in research publications from 2014 to 2024. The United States leads in the volume of publications related to e-Learning pedagogy. VOSViewer facilitates the aggregation of prevalent keywords, revealing four distinct clusters. Prominent keywords identified include "Pedagogy," "E-learning," and "Education”.